Impacts of river discharge, coastal geomorphology, and regional sea level rise on tidal dynamics in Pearl River Estuary - Li, Xia; Cai, Yanzi; Liu, Zezheng; Mo, Xiaobiao; Zhang, Li; Zhang, Cheng; Cui, Baoshan; Ren, Ze (Frontiers in Marine Science, 2023)
Introduction Recently, accelerated sea-level rise (SLR) has raised major concerns on estuarine management and restoration because it modifies estuarine hydrodynamics, such as tidal inundation extent and amplitude, tidal current asymmetry, flood frequency, etc. Understanding underlying processes which regulate estuarine tidal dynamics is critical for mitigating potential impacts on the coastal population and development. Methods We selected the Pearl River Estuary (PRE), an estuary with a higher regional SLR compared to the global SLR as the study area. To identify the effects of regional SLR on tidal dynamics, we analyzed long-term records of four tidal variables from 19 gauge stations between 1952 and 2020, including annual highest tidal levels (AHTLs), annual lowest tidal levels (ALTLs), annual mean tidal ranges (AMTRs), and annual mean tidal levels (AMTLs). Results Results suggested that variability in tidal variables was site-specific. The AMTRs decreased gradually from offshore regions to the upper reaches of rivers with a maximum at the mouth of the estuary. In contrast, the magnitudes of the AHTLs, AMTLs, and ALTLs decreased when approaching the coastline. Distance to the coastline had the highest correlations with the AHTLs, ALTLs, and AMTLs, followed by river width and river depth. The local SLR was responsible for the temporal variability in AHTLs, ALTLs, and AMTLs at the estuarine mouth with correlation coefficients from 0.43 to 0.85 (P < 0.001) but showed low correlations with these three tidal variables at the upper reaches of rivers (P > 0.001). Instead, the tidal variables were highly correlated with river discharge at the upper reaches of rivers, especially for the AHTLs (correlation coefficient = 0.83, P < 0.0001). Conclusions Our study demonstrated that the tidal dynamics demonstrate significant spatial-temporal variability. Geomorphology, river discharge, and sea levels have jointly affected estuarine hydrodynamics.